PENGARUH JENIS BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI DUA VARIETAS BAWANG MERAH(Allium ascalonicum L.) - Dilly Yuda Pebriasih (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
Shallot as a horticultural crop that is widely used in everyday life, shallot have an impact on increasing demand. This study aims to determine the effect of the type of organic matter on the growth and production of shallot plants, the growth of the best shallot varieties with different types of organic matter, and the interaction of the application of organic matter and different varieties on the growth of shallot plants. The research was carried out at the Integrated Field Laboratory, University of Lampung. The treatments were arranged in factorial (2x4) using a randomized block design (RBD) consisting of 8 treatments repeated three times with the first factor being variety (V1=Tajuk variety, V2=Bima brebes variety) and the second factor being organic matter (B1=goat manure). , B2 = cow manure, B3 = cocopeat, B4 = mushroom media waste). To test the homogeneity of the variance of the data using the Barlett test and the Additivity with the Tukey test. After the assumptions were met, the data was processed by analysis of variance and continued with the least significant difference (LSD) test at the 5% level. The results showed that the type of organic matter treatment affected plant height, number of leaves, root length, number of tubers per sample, number of tubers per plot, tuber diameter, tuber wet weight per sample, tuber wet weight per plot. The varietal treatment affected plant height, root length, number of tubers per plot, tuber diameter, tuber wet weight per sample, tuber wet weight per plot. The growth and production of shallots of the Bima Brebes variety and the Tajuk variety were not affected by the type of organic matter used (no interaction occurred).